Development of bio- and eco-composites for the footwear industry - Santos, Palloma Carvalho dos (2018)
Cork composites are often used in several applications including footwear components. The traditional agglomeration process uses a reactive polyurethane-based binder (containing TDI), generating composites with low flexibility and poor water absorption/desorption characteristics, resulting in products with low comfort properties. Furthermore, the presence of TDI, is another important drawback due to its high toxicity. Therefore, the present work is devoted to the development of cork composites, where the TDI-based binder was replaced by an aqueous PUD reinforced with Melissa officinalis L. extract. Cork-composites were produced using different adhesive/cork ratios, and characterized in terms of dimensional stability, water absorption/desorption properties, and mechanical behavior. After the selection of the best adhesive content, composites reinforced with sugarcane bagasse, malt bagasse, coconut fibers, and chia seeds were also produced and characterized.